Elderly Care Provision under National Policy on Older Persons 2013: A Cross-Sectional Study in Dhaka City, Bangladesh - Khatun, Khadiza; Halim, Sadeka (Jagannath University Journal of Science, 2024)
Bangladesh is undergoing a notable demographic transition, characterized by a substantial rise in the proportion of elderly individuals within its population. This demographic transition presents a range of economic, social and cultural issues that necessitate prompt attention and intervention. The aim of this study was to examine the current state of elderly care services and facilities available for older adults in urban landscape by taking into account the ‘National Policy on Older Persons 2013.’ This study was conducted in Dhaka city by employing a cross-sectional study design. The study population covers elderly people aged 60+ years, living in Dhaka City for more than five years continuously and are able to speak well with someone. The study was based on a sample of 240 and the respondents were chosen using convenient sampling technique. The data were collected through face-to-face interview using structured questionnaire and they were analyzed utilizing descriptive statistics. This study found that the existing elderly care services and available opportunities are below the satisfactory level for most of the older adults of the city, even though the ‘National Policy on Older Persons 2013’ was adopted a decade ago. The elderly people in Dhaka city encountered a number of difficulties considering their physical health, psychological and social well-being. In the case of availability of the affordable and quality healthcare services for older adults in their community, 30.4% of the respondents said that the availability, accessibility and affordability of quality healthcare services are very poor, followed by 24.6% below average and 26.3% at the average level. Nearly 75% of the study people said that they had ever experienced unfair treatment for being aged. Indeed, they receive care and support in an inconsistent, disorganized and incoherent manner. The study clearly revealed that there is a need to prioritize person-centered care as well as integrated care system for the effective management of the ageing population in Bangladesh. Jagannath University Journal of Science, Volume 11, Number 1, June 2024, pp. 118−134